System for evaluating investment projects for reconstruction of the housing stock as a component of social protection of the population - BIELIENKOVA, Olha; KOVAL , Oleksandr (Ways to Improve Construction Efficiency, 2025)
Research on a specially developed and improved system for evaluating investment projects for reconstruction and restoration of the housing stock as an important element of social protection of the population. The author analyzes modern approaches to evaluating investment projects in the field of new construction, reconstruction, modernization, housing and communal services, identifies their advantages and disadvantages and offers an improved methodology that takes into account socio-economic factors and covers the interests of different population groups. The article examines the main problems of depreciation of the housing stock, the need for its modernization and reconstruction, and also justifies the significance of investments in this sector from the point of view of ensuring decent living conditions and social security. The author emphasizes the importance of implementing a comprehensive evaluation system that affects financial indicators, social aspects and the environmental component, which meets the principles of sustainable development. The proposed methodology is based on multi-criteria analysis, which allows reducing not only the economic efficiency of the project, but also its social impact, the availability of housing for different categories of the population and improving the quality of life of residents. Particular attention is paid to assessing the risks associated with the implementation of investment projects and developing mechanisms to minimize these risks. It is signed that the implementation of a system for evaluating investment projects for the reconstruction of the housing stock will contribute to increasing the effectiveness of state policy in the field of social protection, attracting private investment and creating favorable conditions for the modernization of the housing sector. The article contains practical recommendations for improving the regulatory framework and mechanisms of state regulation in this area, as well as approaches to ensuring transparency and objectivity of the evaluation process. Thus, the proposed assessment system is a tool that allows ensuring balanced development of housing infrastructure, improving the quality of housing conditions and strengthening social protection of the population through effective planning and implementation of investment projects for the reconstruction of the housing stock.